Companion search around β Pictoris with the newly commissioned L'-band vector vortex coronagraph on VLT/NACO. Issue Volume 8:Issue S299(2013) (6th January 2014) - Mawet, D.; Absil, O.; Milli, J.; Baudoz, P.; Boccaletti, A.; Chauvin, G.; Delacroix, C.; Girard, J. H.; Lagrange, A. M.; O'Neal, J.; Bourget, P.; Forsberg, P.; et al.
Abstract: Here we present the installation and successful commissioning of an L'-band Annular Groove Phase Mask (AGPM) coronagraph on VLT/NACO. The AGPM is a vector vortex coronagraph made from diamond subwavelength gratings tuned to the L' band. The vector vortex coronagraph enables high contrast imaging at very small inner working angle (here 0″.09, the diffraction limit of the VLT at L'), potentially being the key to a new parameter space. During technical and science verification runs, we discovered a late-type companion at two beamwidths from an F0V star (Mawet et al . 2013), and imaged the inner regions of β Pictoris down to the previously unexplored projected radius of 1.75 AU. The circumstellar disk was also resolved from ≃ 1″ to 5″ (see J. Milli et al ., these proceedings). These results showcase the potential of the NACO L-band AGPM over a wide range of spatial scales.